Divergent Patterns of Carbon, Nitrogen, and Phosphorus Mobilization in Forest Soils - Brödlin, Dominik; Kaiser, Klaus; Hagedorn, Frank (Frontiers in Forests and Global Change, 2019)
Carbon (C), nitrogen (N), and phosphorus (P) become released in inorganic or organic forms during decomposition of soil organic matter (SOM), often at varying rates. Our study aimed at identifying the individual patterns and controls of C, N, and P mobilization in soils under beech forests. We exposed organic and mineral horizons sampled along a nutrient availability gradient in Germany to either permanent moist conditions or to dry spells in microcosms and quantified the release of inorganic and organic C, N, and P. In the moist control treatment, releases of DOC, DON and DOP were interrelated and depended on the C:N:P ratio of SOM, whilst net mineralization rates of C, N and P were poorly correlated. Mineralization of C decreased with soil depth from Oi to A horizons, reflecting the increasing SOM stability. Net mineralization of N and P showed divergent depth patterns. In the Oi horizon, microbial immobilization was more pronounced for N than for P. In A horizons, net mineralization of P was less than of N, very likely because of strong sorption of released phosphate by mineral phases. Counterintuitively, net P mineralization in A horizons increased towards P-poor sites, probably due to decreasing contents of clay and pedogenic oxides, and thus, declining P sorption. Drying and rewetting caused stronger mobilization of inorganic and organic P, and organic N than of inorganic C and inorganic N, most likely by lysis of microbial biomass with tight C:N:P ratios. Due to the divergent patterns in N and P cycling, the organic layer is more important for the mineralization of P than the mineral soil; for N the mineral soil is most relevant. Consequently, the loss of the organic layer would deteriorate P nutrition, in particular at nutrient-poor sites. Overall, our results indicate that the cycling of C, N, and P is not directly coupled due to the different microbial processing and, in the mineral soil, differential sorption of N and P. This may ultimately cause imbalances in the N and P nutrition of forests.